(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The problem of the active participation of modern landscape architecture in the creation of a recreational environment for business centers in Uzbekistan is being studied. Examples of various public and business spaces are analyzed, conclusions are made about the role of landscape architecture in solving the problem under consideration, and the principles of creating the aesthetics and comfort of this recreational environment of business centers are systematized